The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10803-020-04587-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Visual Perceptual Load on Auditory Awareness of Social vs. Non-social Stimuli in Individuals with Autism

Abstract: This study examined the effect of increasing visual perceptual load on auditory awareness for social and non-social stimuli in adolescents with autism spectrum disorder (ASD, n = 63) and typically developing (TD, n = 62) adolescents. Using an inattentional deafness paradigm, a socially meaningful ('Hi') or a non-social (neutral tone) critical stimulus (CS) was unexpectedly presented under high and low load. For the social CS both groups continued to show high awareness rates as load increased. Awareness rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Some studies report little evidence of differences in the frequency or accuracy of looks to social stimuli (191) inviting the conclusion that social attention is typical in older individuals. However, other studies suggest that social attention remains less efficient or more effortful in older individuals with ASD (156,(192)(193)(194); Liu et al, (in submission). Indeed, one recent study suggests that adolescents with ASD may display less efficient covert processing of eye contact (195).…”
Section: Motivation and Social Attention In Older Individualsmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies report little evidence of differences in the frequency or accuracy of looks to social stimuli (191) inviting the conclusion that social attention is typical in older individuals. However, other studies suggest that social attention remains less efficient or more effortful in older individuals with ASD (156,(192)(193)(194); Liu et al, (in submission). Indeed, one recent study suggests that adolescents with ASD may display less efficient covert processing of eye contact (195).…”
Section: Motivation and Social Attention In Older Individualsmentioning
confidence: 98%
“…Heightened interest and attention to non-social objects, rather than a diminished salience for faces, may also be central to motivation factors that impact the social attention symptoms of young children with ASD (12,(155)(156)(157). This pattern of perceptual bias could result in diminished social attention and eye contact effects, but for reasons very different from those described in "social" motivation models.…”
Section: Social Motivation and The Bi-directional Nature Of Social Attentionmentioning
confidence: 99%
“…In short, learning by autistic children in our task was not necessarily facilitated by providing a greater amount of external feedback (adding extraneous elements to the task) but rather by providing a greater amount of task-relevant information at the same time. An advantage in perceptual capacity in autism, as has been found in a growing literature (Remington et al, 2012;Remington & Fairnie, 2017;Remington et al, 2019;Tillmann et al, 2021), would give autistics an ability to process more information at once, suggesting that the free availability of more information to learn from, versus the use of extraneous feedback, would benefit autistics. This is consistent with the direction of our findings, which also showed that learning strategies were similar across groups, leaving group differences in performance across learning situations that were not accompanied by group differences in the strategies examined here.…”
Section: Access To and Manipulation Of Informationmentioning
confidence: 84%
“…If these influential views and practices are well-founded, autistic performance should not benefit from, and possibly be hindered by, large quantities of simultaneously presented information during an implicit learning task. Alternatively, a growing body of evidence demonstrates that autistics have an increased, not decreased, perceptual capacity (Remington et al, 2012; Remington & Fairnie, 2017; Remington et al, 2019; Tillmann et al, 2021), which may benefit autistic learning when more, rather than less, information necessary to solve a task is made available at the same time. In the same direction, autistics may particularly benefit from situations allowing them the latitude to process and combine quantities of information across different levels and scales, from small details to large displays (Mottron et al, 2009, 2013).…”
mentioning
confidence: 99%
“…Our SSP assessment found that ASD children are often di cult to concentrate in noisy environments, emphasizing the obstacles in their auditory ltering and auditory attention. And this weakness is more obvious in the recognition of human voice [48] , which may be an important explanation for autistic individuals' lack of attention preference for social stimulation [49] .…”
Section: Asd Sensory Predicts Social Disordermentioning
confidence: 99%